Estrategia metodológica para desarrollar la lectura comprensiva en los niños de quinto año de educación básica de la asignatura de lengua y literatura en la escuela de educación general Básica “González Suárez” provincia Bolívar cantón chimbo parroquia San Sebastián periodo académico 2023- 2024 - García Carrasco, José Alejandro (2024)
Comprehensive reading is a fundamental skill in the academic and personal development of students as it allows them to understand and interpret the text read and link the knowledge acquired during academic training with real-life situations. For this reason, the present research work has carried out a study on the methodological strategies with the students of the fifth year of basic general education of the “González Suarez” Basic Education School of the Chimbo canton with the main objective of developing the basic skills of reading comprehension through the adaptation of a methodological proposal in language and literature with the purpose of strengthening the critical and reflective thinking of students. To achieve this, a qualitative approach has been applied through information processing from the Atlas.ti software. from the interviews conducted with students, teachers, and parents. All to achieve a comprehensive perspective of the object of study and provide the most suitable solutions to face the learning difficulties existing in the context.